PEMERIKSAAN KANDUNGAN ZAT KIMIA FORMALIN PADA BAKSO IKAN DAN TAHU - Tuti Handayani; Sherly Mutiara (Jurnal Katalisator, 2020)
Formaldehyde a toxic chemical compound. Formaldehyde is prohibited for use in food according to the RI Minister of Health Regulation No.033 of 2012 concerning food additives. Meatballs, Fish and Tofu are protein sources of food. This material is easily damaged by microorganisms. There have been many cases of formaldehyde found in food products in Indonesia. The purpose of this study was to determine the presence or absence of formaldehyde in fish, meatball and tofu before and after providing health education. the method used in this study is an experimental method using a Qualitative Analysis approach. The results obtained were found 16Â  samples (fish and dry fish) is positive of formaldehyde. after providing education to traders the 15 samples still found in the market. That means counselling is not effective as an effort to eliminate formaldehyde in food products.